The paradox of special autonomy: Why does wealth make Papua poor? - Hendy Setiawan; Choirunnisa Choirunnisa (Masyarakat, Kebudayaan dan Politik, 2023)
Papua’s Special Autonomy has been running for two decades with a budget disbursement of approximately 101.2 trillion rupiah. In line with that, this study aims to analyze the problems that occurred in Papua during the implementation of special autonomy. This research is qualitative research using data from books, journals, and media reports. This research adopts Bardhan and Mookherjee’s theory about the condition of fiscal decentralization which generates welfare. The research results substantially consist of two main things. First, from the point of view of local democracy, previously the special autonomy policy in Papua had not fully involved local (customary) figures in managing the special autonomy fund. Second, special autonomy in Papua has made budget items increase, both from central to regional transfer funds or other balancing funds. However, this fiscal authority is not accompanied by good capacity building for the organizers of the special autonomy for Papua. Therefore, it can be concluded that the implementation of special autonomy for Papua over the last two decades has not been able to function local democracy and produce reliable fiscal authorities so that the road to prosperity is still long.